Low Density Wood Impregnation with Water-Repellent Organosilicic Compounds - Canosa, Guadalupe (2018)
Many protective treatments for low density wood are applied by impregnation to give water-repellency and to control pathologies that usually have this substrate. The properties of Araucaria angustifolia, chemically modified by impregnation with methyltriethoxysilane, n-octyltriethoxysilane and mixtures of both in several ratios, were investigated to achieve mainly high dimensional stability, low capillary water absorption as well as satisfactory water vapor permeability. The aforementioned impregnants produce the wood chemical modification, involving the reaction of hydroxyl groups of the wood with the hydrolysis products of alcoxysilanes. It is concluded that the organosilicon polymers allow improving important characteristics of wood: 1) the non-occlusive coating keeps the water vapor permeability unaltered; 2) the alkoxysilane type defines the hydrophobicity and the continuity of coating formed on the pore wall and finally; 3) the polymeric structure formed after finishing sol-gel process incises both on the capillary water absorption and the dimensional stability. In addition, the studied treatments have the advantage of allowing that the water vapor, which permeates through the organosilicon coating placed on cell wall, can exit by hydrophobic repulsion and thus, prevent faults appearance generated by the condensed water inside of wood.